2017
DOI: 10.3892/or.2017.5713
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Skp2 suppresses the proliferation and invasion of osteosarcoma cells

Abstract: Abstract. Osteosarcoma (OS) is a common bone tumor that mainly affects children and young adults. S-phase kinase-associated protein 2 (Skp2) has been characterized to play a critical oncogenic role in a variety of human malignancies. However, the biological function of Skp2 in OS remains largely obscure. In the present study, we elucidated the role of Skp2 in cell growth, cell cycle, apoptosis and migration in OS cells. We found that depletion of Skp2 inhibited cell growth in both MG-63 and SW 1353 cells. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…We found that F‐box proteins Skp2 and β‐TrCP2, which are also known to be oncoproteins, are important to maintain the proliferation of GCPs. This finding is consistent with the known role of these molecules in enhancing cell proliferation in various cancers (Ding et al., 2017; Nakayama et al., 2004; Wang et al., 2018; Zhang et al., 2016; Zhong et al., 2013). However, it is possible that other F‐box proteins are also involved in proliferation and differentiation of GCPs because approximately 70 F‐box proteins are reported in mammals.…”
Section: Discussionsupporting
confidence: 89%
“…We found that F‐box proteins Skp2 and β‐TrCP2, which are also known to be oncoproteins, are important to maintain the proliferation of GCPs. This finding is consistent with the known role of these molecules in enhancing cell proliferation in various cancers (Ding et al., 2017; Nakayama et al., 2004; Wang et al., 2018; Zhang et al., 2016; Zhong et al., 2013). However, it is possible that other F‐box proteins are also involved in proliferation and differentiation of GCPs because approximately 70 F‐box proteins are reported in mammals.…”
Section: Discussionsupporting
confidence: 89%
“…70 ) and SKP2 (ref. 71 )) have been successfully developed using this type of enzymes. However, several E3 ubiquitin ligases such as SMURF1 , SMURF2 , ARKADIA , SYNOVIOLIN , NEDD4 , and PELLINO1 (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of our investigation, Ding and colleagues reported that overexpressing Skp2 leads to enhanced cellular growth, motility, and invasion in osteosarcoma, while increased apoptosis was observed in cell lines depleted of Skp2 42 , 43 . Although these authors did not analyze Skp2 in an in vivo model, their findings certainly corroborate our hypothesis that Skp2 plays an important oncogenic role in osteosarcoma pathobiology.…”
Section: Discussionmentioning
confidence: 84%